Pressure drop and mixing behaviour of non-Newtonian fluids in a static mixing unit - Kumar G.; Upadhyay S.N. (My University, 2025)
Static or motionless mixers have received wide application in chemical and allied industries due to their low cost and high efficiency. The pressure drop and mixing behaviour of such mixers have been widely studied. However, the available information for non-Newtonian fluids is scanty. The results of pressure drop and mixing studies conducted with a locally made motionless mixer (MALAVIYA mixer) and four non-Newtonian fluids-aq. CMC, PVA, and PEG solutions are reported in this article. The new mixer causes less pressure drop compared to some of the commercial mixers. Mixing behaviour of the unit is more closer to plug flow and a two-parameter model correlates the dispersion data. © 2008 Canadian Society for Chemical Engineering.